South Korea needs more big company jobs - Young-sun Koh (Korea Development Institute (KDI), 2024)
South Korea stands out among OECD countries for its lowest proportion of jobs in large enterprises. Good jobs, often synonymous with employment opportunities in large enterprises, are in short supply. This shortage prompts various societal issues: the overheating of college admission competition, a decline in social mobility, decreased birth rates, stagnating employment rates for women, and increased concentration in the capital area. There is a pressing need to identify and address policy barriers to company scale-up.
Keywords: 330